2000
DOI: 10.2337/diabetes.49.7.1239
|View full text |Cite
|
Sign up to set email alerts
|

Induction of endothelin-1 expression by glucose: an effect of protein kinase C activation.

Abstract: Enhanced actions or levels of endothelin-1 (ET-1), a potent vasoconstrictor, have been associated with decreased blood flow in the retina and peripheral nerves of diabetic animals and may be related to the development of pathologies in these tissues. Hyperglycemia has been postulated to increase ET-1 secretion in endothelial cells. We have characterized the mechanism by which elevation of glucose is increasing ET-1 mRNA expression in capillary bovine retinal endothelial cells (BREC) and bovine retinal pericyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(124 citation statements)
references
References 49 publications
(73 reference statements)
1
118
0
5
Order By: Relevance
“…A 4.8 Ϯ 0.6-fold increase in PAI-1 promoter activity was observed in mesangial cells incubated with 2 mM glucosamine for 4 days. Pretreatment with the general PKC inhibitor, GF109203X (5 M) (9,12), diminished this to 1.5 Ϯ 0.3-fold (p Ͻ 0.01), but many chemical kinase inhibitors lack specificity (67). To confirm these results and address the roles of individual PKC isoforms, we cotransfected expression vectors for kinaseinactive, DN-PKC mutants with PAI-LUC.…”
Section: Glucosamine-induced Pai-1 Promoter Transcriptionmentioning
confidence: 92%
See 1 more Smart Citation
“…A 4.8 Ϯ 0.6-fold increase in PAI-1 promoter activity was observed in mesangial cells incubated with 2 mM glucosamine for 4 days. Pretreatment with the general PKC inhibitor, GF109203X (5 M) (9,12), diminished this to 1.5 Ϯ 0.3-fold (p Ͻ 0.01), but many chemical kinase inhibitors lack specificity (67). To confirm these results and address the roles of individual PKC isoforms, we cotransfected expression vectors for kinaseinactive, DN-PKC mutants with PAI-LUC.…”
Section: Glucosamine-induced Pai-1 Promoter Transcriptionmentioning
confidence: 92%
“…High glucose results in de novo synthesis of diacylglycerol and membrane translocation of various PKC isoforms, including PKC-␣, -␤I, -␦, -⑀, and -in mesangial and other cells in vitro and in experimental animals (6 -13). In addition, there is good evidence that these activated PKC isoforms contribute to high glucose-induced increases in gene transcription and participate in the pathogenesis of diabetes complications (6,9,11,12,14,26,27,62).…”
mentioning
confidence: 99%
“…of Molecular Biology, Kyung Hee University College of Medicine, Seoul, Korea). Adenoviruses containing either ␤-galactosidase (Ad-␤-gal) or a mixture of dominant-negative ␣1 AMPK and ␣2 AMPK (Ad-DN-AMPK) were added to subconfluent C2C12 cells at a concentration of 50 plaque-forming units per cell for 2 h at 37°C in Dulbecco's modified Eagle's medium without serum, as described previously (32).…”
Section: Materials-␣-msh Ndp-msh and [Glumentioning
confidence: 99%
“…receptor expression and nitric oxide (NO) production by activation of endothelial NO synthase (eNOS); however, the direction of these changes is unclear [3]. Recently, it has been shown that high glucose increases ET-1 mRNA and protein expression mediated partially by activation of protein kinase C (PKC) β and δ isoforms in bovine retinal endothelial cells [4]. …”
Section: Introductionmentioning
confidence: 99%